2020
DOI: 10.1038/s41398-020-00944-w
|View full text |Cite
|
Sign up to set email alerts
|

Embracing the positive: an examination of how well resilience factors at age 14 can predict distress at age 17

Abstract: One-in-two people suffering from mental health problems develop such distress before or during adolescence. Research has shown that distress can predict itself well over time. Yet, little is known about how well resilience factors (RFs), i.e. those factors that decrease mental health problems, predict subsequent distress. Therefore, we investigated which RFs are the best indicators for subsequent distress and with what accuracy RFs predict subsequent distress. We examined three interpersonal (e.g. friendships)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Further, at least one study has used network methodology to examine variation in a psychiatric disorder (psychosis) across types of early childhood trauma (Isvoranu et al, 2017). In a line of investigation converse to our own, Fritz, Fried, Goodyer, Wilkinson, and Harmelen (2018;2020) examined network relationships among protective resilience factors in the aftermath of childhood adversity, with important outcomes for mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Further, at least one study has used network methodology to examine variation in a psychiatric disorder (psychosis) across types of early childhood trauma (Isvoranu et al, 2017). In a line of investigation converse to our own, Fritz, Fried, Goodyer, Wilkinson, and Harmelen (2018;2020) examined network relationships among protective resilience factors in the aftermath of childhood adversity, with important outcomes for mental health.…”
Section: Introductionmentioning
confidence: 99%
“…We decided to use factor scores rather than sum scores to avoid tau-equivalence and to reduce measurement error (for a rationale see Additional file V Part A in Fritz, Stochl et al, 2019a 8 ). We pooled over the resulting factor scores and fit indices and extracted the resulting pooled factor scores for further analyses (see Supplement I in Fritz Stochl et al 2019b 9 for details). In sum, we could conduct the main analyses on 1130 participants, as those could be included in the imputation analyses (n = 1188) and had data for CA (n = 1139).…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, we showed that most of the 10 RFs were not only concurrently associated with less mental health problems, but also three years later. 8,9 More specifically, the RFs predicted mental distress three years later similarly well as mental distress could predict itself. 9 Hence, there is good support showing that most of the 10 RFs do indeed reduce distress; or in other words, that RFs have a direct, negative effect on mental health problems.…”
Section: An Empirical Examination Of How Resilience Factors Mitigate the Effect Of Childhood Adversity On Adolescent Mental Healthmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, according to Konaszewski and colleagues, resilience is essential in helping adolescents achieve well-being by reducing the focus on negative emotions [ 37 ]. Fritz and colleagues supported this assertion by showing that lower levels of resilience at an earlier age predicted higher distress later in adolescence [ 44 ]. Additionally, Hildebrand and colleagues reported more internalizing and externalizing problems in children and adolescents with lower levels of resilience [ 45 ].…”
Section: Introductionmentioning
confidence: 99%